The Contemporary Issues On Fatwa Management In A Secular State: The Philippine Experience - Mariam S. Tagoranao; Alizaman D. Gamon; Zubaidi Wahyono (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
E-PROCEEDING 3rd INTERNATIONAL CONFERENCE OF THE POSTGRADUATE STUDENTS AND ACADEMICS IN SYARIAH AND LAW 2020 (3rd INPAC 2020) "Syariah and Law Approach in Solving Contemporary Issues" Organized by: Faculty of Syariah and Law Date: 18 November 2020